2014
DOI: 10.1016/j.cgh.2014.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Emergency Department Patients With Crohn's Disease Could Reduce Computed Tomography Use by Nearly Half

Abstract: Background/Aims Computed Tomography (CT) is a useful tool in Crohn’s disease (CD) to assess disease activity and exclude complications. Excessive radiation has been associated with increased risk of malignancy. We aimed to identify automatable algorithms with a high negative predictive value (NPV) of a significant CT finding in patients with CD presenting to the emergency department. Methods We conducted a retrospective review of a tertiary center’s medical records to identify adults with a diagnosis of CD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 8 publications
1
27
1
Order By: Relevance
“…1,2,13,20 However, we found that almost 50% of patients had a clinically significant CT finding. This higher incidence is likely due to a more inclusive definition of what constitutes a CD-related CT finding (abscess, fistula, stricture, perforation, bowel obstruction), in addition to including non-CD related findings (i.e.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…1,2,13,20 However, we found that almost 50% of patients had a clinically significant CT finding. This higher incidence is likely due to a more inclusive definition of what constitutes a CD-related CT finding (abscess, fistula, stricture, perforation, bowel obstruction), in addition to including non-CD related findings (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…14 The estimated use of CT scans in the ED to assess patients with CD ranged from 26–47% in 2001 to 42–78% in the late 2000s. 1,2 While CT scans can be essential in the diagnosis of enteric fistulas, abscesses, or perforations, and are as accurate as other imaging modalities, there is a risk of overutilization. 513 Patients presenting to the ED with abdominal pain are undergoing twice as many CT scans in comparison to a decade ago, yet the number of clinically significant findings and admissions have not significantly changed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive use of CT imaging in IBD patients presenting to the emergency department (ED) has also raised concern. In a study from the United States, no significant findings were observed in 32.8% of CT imaging studies carried out in IBD patients in the ED [31] . Preliminary algorithms to avoid inappropriate use of CT imaging in IBD patients presenting to the ED have been proposed and require validation [31,32] .…”
Section: Ulcerative Colitismentioning
confidence: 99%